2004
DOI: 10.1007/s11661-004-0133-5
|View full text |Cite
|
Sign up to set email alerts
|

In-situ observations of low-cycle fatigue damage in cast AM60B magnesium in an environmental scanning electron microscope

Abstract: We present in-situ observations of low-cycle fatigue damage in cast AM60B magnesium. The in-situ fatigue tests were conducted in an environmental scanning electron microscope under both high vacuum and 20 Torr of water vapor. In both environments, fatigue cracks were observed to form and grow within the dendrite cells and through the interdendritic regions. Crack formation and growth through the dendrite cells proceeded along persistent slip bands. The persistent slip bands were typically oriented at about 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Furthermore, the wavy appearance of slip lines is characteristic of the cross-slip of o a4 -type dislocations into non-basal slip planes [55]. These findings are in agreement with macroscopic flow curves presented earlier, as well as crack initiation mechanisms reported for various magnesium alloys in the literature [56][57][58][59][60].…”
Section: Fracture Surface Characterisationsupporting
confidence: 91%
“…Furthermore, the wavy appearance of slip lines is characteristic of the cross-slip of o a4 -type dislocations into non-basal slip planes [55]. These findings are in agreement with macroscopic flow curves presented earlier, as well as crack initiation mechanisms reported for various magnesium alloys in the literature [56][57][58][59][60].…”
Section: Fracture Surface Characterisationsupporting
confidence: 91%
“…Multiple investigators [1][2][3][4][5] have demonstrated via computational methods that the underlying microstructure attributes (i.e., grain size and orientation distributions, surface proximity of pre-existing defects and twinning) can be largely responsible for the variability in fatigue life in several engineering alloys. Cyclic loading at low to medium applied strain amplitudes below the macroscopic yield point induces cyclic plastic deformation patterns that are highly inhomogeneous through the microstructure and results in significant variability and uncertainty in fatigue life estimation.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of intergranular and transgranular [7,8] crack path in Mg alloys is discussed by various authors. The role of microporosity as the crack initiation source is found in fatigue analysis of Mg alloys [9][10][11][12][13]. Magnesium and its alloys exhibits moderate ductility due to the lack of independent slip systems [14] also influence this materials' fracture behaviour.…”
Section: Introductionmentioning
confidence: 99%